Treatment sequences in BRAF-V600-mutated NSCLC: first-line targeted therapy versus first-line (chemo-) immunotherapy - Wiesweg, Marcel; Alaffas, Ali; Rasokat, Anna; Saalfeld, Felix Carl; Rost, Maximilian; Assmann, Christin; Herster, Franziska; Hilbrandt, Moritz; Griesinger, Frank; Kron, Anna; Roeper, Julia; Glanemann, Franziska; et al. (Journal of thoracic oncology, 2025)
Background - Targeted treatment of patients with metastatic BRAF-V600-mutated NSCLC using BRAF/MEK-inhibitors is effective but limited by acquired resistance. Patients with BRAF-mutant NSCLC may derive long-lasting benefit from immune checkpoint inhibition with programmed death-1/programmed death-ligand 1 (PD-L1) antibodies (immuno-oncology [IO]). Although IO is the preferred first-line therapy in BRAF-mutated melanoma, the optimal treatment sequence in BRAF-mutated NSCLC is not defined. - Methods - This retrospective study investigated the clinical outcome of patients with metastatic BRAF-V600-mutated NSCLC diagnosed in the German national Network Genomic Medicine Lung Cancer. - Results - We identified 205 patients with BRAF-V600-mutated NSCLC; 175 patients received first-line therapy with dabrafenib/trametinib (DAB/TRM, 65.1%), IO alone (19.4%), or chemotherapy-IO (15.4%). Overall survival (OS) and time-to-treatment failure of first-line therapy was identical for patients receiving first-line DAB/TRM (median OS 28.0 months) or chemo/IO (27.8 months, hazard ratio [HR] 1.1, p = 0.68). Female patients had superior OS (HR 0.65, p = 0.049, confirmed in multivariate model), which was mainly driven by superior OS of female to that of male patients receiving first-line DAB/TRM (OS HR 0.53, p = 0.015). There was no sex difference in survival of patients receiving IO-based first-line treatment (OS HR 1.02). Surprisingly, high PD-L1 status (tumor proportion score ≥50%) was associated with shortened time-to-treatment failure in first-line treatment (HR 1.83, p = 0.002, confirmed in multivariate models adjusting for sex; OS with nonsignificant trend, HR 1.4), regardless of whether the first-line regimen was IO-based or targeted therapy. - Conclusions - Targeted or IO-based first-line treatment of BRAF-V600-mutated NSCLC has similar survival outcomes. Sex and PD-L1 status may support decision-making at the individual patient level.